The Effect of Human Resource Development, Work Culture, and Organizational Commitment on Employee Performance (A Study of the General Elections Commission of Tanah Bumbu Regency) - Muhammad Tiar; Ahmad Widyan Albajili; Muhammad Trio Taruna (Magister Administrasi Bisnis ULM, 2026)
Abstract: This study aims to analyze and examine the effects of human resource development, work culture, and organizational commitment—simultaneously, partially, and dominantly—on the performance of employees at the General Elections Commission (KPU) of Tanah Bumbu Regency. This research employs an explanatory research design. The population of the study consists of all civil servants and contract (honorary) employees, with a total sample of 70 respondents selected using a saturated sampling technique. Data were collected through questionnaires, and the research instruments were tested for validity and reliability. Data analysis was conducted using multiple linear regression analysis, including the t-test, F-test, and coefficient of determination (R²). The results indicate that simultaneously (F-test), human resource development, work culture, and organizational commitment have a significant effect on employee performance at the Tanah Bumbu Regency KPU. Partially (t-test), human resource development and organizational commitment have a positive and significant effect on employee performance, while work culture does not have a significant partial effect. Furthermore, organizational commitment was found to be the dominant factor influencing employee performance, with a contribution of 48.6%. The coefficient of determination (Adjusted R²) is 0.488, indicating that 48.8% of employee performance can be explained by the variables included in this study, while the remaining 51.2% is influenced by other factors not examined in this research